Risk Factors of Anemia in Pregnant Women in Baktiraja Health Center Region, Humbang Hasundutan - Purba, Edy Marjuang; Dewi, Eva Ratna; Jelita, Fitri (Sari Mutiara Indonesia University Press, 2018)
Indonesia Basic health research in 2017 states that maternal mortality rate was still high (359 per 100,000 live births) and the main cause was bleeding due to anemia, (35.1%). Beside has impact on maternal health, anemia also has a bad effect on babies, namely premature birth, low birth weigh, slow growth and low intelligence levels. The proportion of anemia in Baktiraja Public Health Center increased from 2015 (25.7%) to 2016 (29.3%). This study aims to determine risk factors of anemia in pregnant women in the Baktiraja Health Center region, Humbang Hasundutan District in 2017. This was an observational analytic study with unmatched case control design. Population was all pregnant women in region of Baktiraja health center . The total sample was 114 consisting of 57 cases and 57 controls. Cases were all pregnant women who ever had Hb level <11 g/dl during pregnancy while controls were pregnant women who had Hb level ≥11 g/dl during pregnancy that taken with systematic random sampling. Data were analyzed by bivariate analysis through chi-square test and multivariate analysis through logistic regression. Bivariate analysis showed that education (p = 0.015, OR = 2.547, 95% CI = 1.423-3.458), knowledge(p = 0.002, OR = 3.578, 95% CI = 1.815-4.519), age (p = 0.007, OR = 3,292, 95% CI = 1.563-3.811), comsumption of iron tablet (p = 0.011, OR = 2.787, 95% CI = 1.543-3.622), antenatal visit (p = 0.001, OR = 3.818, 95% CI = 1.96-4.875) were significantly associated with anemia. Parity, income status, and distance of pregnancy did not associate with anemia (p≥0,05). Multivariate analysis showed that antenatal visit had most significantly association with anemia (p = 0.018, OR = 2.117, 95% CI = 1.545-3.839). Irregular antenatal visit was the strongest risk factor of anemia during pregnancy period. It wa suggested to Baktiraja health center to increase knowledge and awareness of pregnant women about prevention of anemia and also the importance regular antenatal visit for monitoring Hb level every trimester. It was also suggested to Baktiraja Health Center staff to control comsumption of iron tablet so that pregnant women who do not consume iron tablets regularly can be warned quickly.